Concrete properties containing fine aggregate marble powder - Alyamac, Kursat Esat; Aydin, Alp Bugra (Korean Society of Civil Engineers-Ksce, 2015)
The rapid growth of the marble industry introduces concerns regarding the negative impact of marble quarrying on the environment, because the cutting of marble creates sludge. The incorporation of marble sludge (powder) into concrete and cement-based products would make significant environmental and economic contributions. This study aims to develop a concrete mixture with maximum marble content that has strength properties comparable to that of the non-marble reference concrete (without marble powder), as opposed to developing a marble powder concrete with maximum compressive strength. The main purpose is to replace sand with marble powder in concrete because such a mixture will be environmentally friendly and economically feasible. The concrete samples are produced by replacing sand with marble powder at 10%, 20%, 30%, 40%, 50% and 90% by volume. The compressive strength values are determined after 7, 28 and 90 days with splitting tensile strength values at 28-th day including water absorption and abrasion resistance values. A feasibility evaluation is performed using parameters such as fresh concrete, compressive strength, sorptivity, abrasion resistance, and estimated cost. Based on the feasibility evaluation it is shown that using up to 40% marble powder in concrete is suitable in accordance with the requirements.
Keywords: concrete; strength; marble powder; waste; durability; feasibility evaluation